Heavy Metal Content in Hair at Workers in Gas Station of Sidoarjo City in 2021: Kandungan Logam Berat pada Rambut Petugas Stasiun Pengisian Bahan Bakar Umum (SPBU) di Sidoarjo pada Tahun 2021 - Rohmah, Jamilatur; Miranda, Niken Anggita; Marlina, Mariany Lambertine; Fiya, Uus Ufita (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
One of the most dominant workplaces where heavy metal contamination occurs is the Gas Station (SPBU). Gas station workers are at high risk of being exposed to heavy metals while working due to inhaling fuel that evaporates into the air and vehicle fumes due to the behavior of motorists who do not turn off the engine while waiting in line. Determination of the level of heavy metal contamination of Zn, Cu, Pb, Cd, Fe, and Cr was determined through hair clippings using the Atomic Absorbtion Spectrophotometry (AAS) method. The gas stations used in this study are SPBU X and Y in Sidoarjo. This study aims to determine the levels of heavy metals in hair and to determine the relationship between working period, age, smoking habits, and savety with heavy metal levels in gas station workers in Sidoarjo. The type of research used is descriptive cross sectional and analytical method through filling out questionnaires and correlative statistics with SPSS. The results obtained showed that the average levels of heavy metals Zn, Cu, Pb, Cd, Fe, and Cr at SPBU X were 0.232, respectively; 0.000; 0.003; 0.001; 0.464; and 0.024 mg/g. while the average levels of heavy metals Zn, Cu, Pb, Cd, Fe, and Cr at SPBU Y were 0.516, respectively; 0.000; 0.007; -0.001; 0.345; and 0.051 mg/g. It can be said that the levels of heavy metals Zn, Cu, Pb, Cd, Fe, and Cr did not exceed the specified threshold. The results of the statistical test of the correlation between the levels of heavy metals Zn, Cu, Pb, Cd, Fe, and Cr with years of service, age, smoking habits, and PPE of gas station workers were not significant (p>0.05).